PENGARUH CITY BRANDING DAN CITY IMAGE TERHADAP KEPUTUSAN BERKUNJUNG SERTA DAMPAKNYA PADA MINAT BERKUNJUNG KEMBALI KE KOTA MADIUN - Eva Mirza Safitri; Aminudin Azis; Prasetyo Yekti Utomo (Epicheirisi: Jurnal Manajemen, Administrasi, Pemasaran dan Kesekretariatan, 2022)
The objectives of this research are to explain the effect of City Branding (X1) on Visiting Decisions (Y); City Image (X2) Against Visiting Decisions (Y); Decision to Visit (Y) on Interest in Revisiting (Z) ; City Branding (X1) Against Revisit Interests (Z) ; City Image (X2) Against Visiting Interest (Z) ; City Branding (X1) Against Revisit Interests (Z) Through Mediation of Visiting Decisions (Y); and The Influence of City Image (X2) on Interest in Returning (Z) Through Mediation of Visiting Decisions (Y) This study uses a quantitative approach with an explanatory method. Sources of data used in the form of primary data obtained from the results of the assessment of respondents' answer scores using a Likert scale. Data was collected by distributing questionnaires to 100 respondents. The measurement of City Branding variable (X1) uses indicators based on Simon Anholt's Hexagonal City Branding theory, City Image variable (X2) uses indicators based on Boulding theory, Visits Decision Variable (Y) uses indicators based on Cleverdon theory, while Visiting Interests Returns variable (Z) uses indicators based on Hellier's theory. The results show that the first hypothesis is proven, the second hypothesis is not proven, the third hypothesis is proven, the fourth hypothesis is proven, the fifth hypothesis is not proven, the sixth hypothesis is not proven, and the seventh hypothesis is not proven. Keywords: City Branding, City Image, Decision to Visit, Interest in Visiting